2021
DOI: 10.18280/ijht.390510
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Air Conditioning Unit under Constant Outdoor Wet-Bulb Temperature and Varied Dry-Bulb Temperature

Abstract: An experiment has been carried out for examining the performance of an air conditioning unit under constant outdoor wet-bulb temperature and varied dry-bulb temperature. During the experiment, the wet-bulb temperature of the compartment for outdoor unit was maintained at 22℃ and the dry-bulb temperature was varied from 24℃ to 36℃. The increase of outdoor air temperature results in the increase of supply air temperature, discharge temperature, suction temperature, and liquid line temperature. These cause the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
5
11
0
Order By: Relevance
“…It means that the dependence of suction temperature on the outdoor air temperature can be expressed in a linear equation with a strong correlation. For a comparison, the similar range of suction temperature from 10.52℃ to 11.62℃ were reported for an experiment with varied DBT and constant WBT [23]. This increases the suction temperature by about 0.1℃ for each 1℃ of the increase of outside air DBT.…”
Section: Suction and Discharge Temperaturesupporting
confidence: 59%
See 1 more Smart Citation
“…It means that the dependence of suction temperature on the outdoor air temperature can be expressed in a linear equation with a strong correlation. For a comparison, the similar range of suction temperature from 10.52℃ to 11.62℃ were reported for an experiment with varied DBT and constant WBT [23]. This increases the suction temperature by about 0.1℃ for each 1℃ of the increase of outside air DBT.…”
Section: Suction and Discharge Temperaturesupporting
confidence: 59%
“…Also, for every 1℃ increase in outside air temperature, the energy efficiency ratio and cooling capacity were reduced by 2.1% and 1.0%, respectively. Another study was carried out by varying ambient air DBT (dry-bulb temperature) and maintaining outdoor WBT (wet-bulb temperature) at a constant value [23]. From this study, for every 1℃ increase in outside temperature, the input power increased by 1.4%, cooling capacity decreased by 0.8%, and COP decreased by 2.0%.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the measurement inside the pipe was confirmed by previous publications. Setyawan et al, [14] reported a range of suction temperature from about 9 to 11C when the air conditioner was operated at outside air temperature from 32 to 38C. Discharge temperature of about 98C was reported by Esbrí et al, [15] from their experiment with R134a and IHX at condensing temperature of 40C and evaporating temperature of -4.7C.…”
Section: Suction and Discharge Temperaturementioning
confidence: 91%
“…The result of the second method of temperature measurement is more accurate than that of the first method. Standardized test based on ISO 5151: 2017 measured the input power to operate the similar capacity of air conditioner at averagely 920 Watt and 912 W [14,22]. It should be noted that the last two publications included power for operating the condenser and evaporator fans that consumed about 50 Watts.…”
Section: Powermentioning
confidence: 99%
See 1 more Smart Citation